Strategic planning for sustainable wetland tourism in Setiu, Terengganu using Building Information Modelling (BIM) / Siti Nur Hidyatul Ain M. Nashruddin ... [et al.] - M. Nashruddin, Siti Nur Hidyatul Ain; Herman, Siti Sarah; Mohd Nashruddin, Siti Nur Ashakirin; Ismail, Sumarni; May Ling, Siow (2022)
The sustainability of tourism industry is critically important especially during the pandemic since early 2020. With the diffusion of information and communication technology in the industry, Building Information Modelling (BIM) is widely adopted in tourism industry. However, the systematic implementation of BIM in tourism industry experiences challenges. This study aims to develop strategic planning by implementing BIM in Setiu wetland, Terengganu, Malaysia within the tourism industry context. Initially, the strategies are drawn from a comprehensive review of the relevant literature. Through an interview with 8 effective expertise from the BIM modeller, town planner, architecture, engineer, contractor (AEC), project manager, programme manager and Setiu wetland person in charge (expertise). Seven critical strategies were identified which are, clearly defined plans and objectives for BIM implementation, financial support, capabilities and skills in using BIM, collaborative working to BIM execution, managing changes and risks in projects, organizational and delivery measures to ensure BIM implementation, government policy and incentives to promote BIM implementation. The further principal component analysis groups the strategies and finds latent factors of the strategies, including institutional governance, change accommodation, technical environment, cooperation, and resources. This finding reveals that systematic BIM implementation is inevitably associated with the tourism industry context and indicates that the enhancement of current BIM implementation in industry covers the strategies of the technical, institutional, and managerial aspects to accommodate changes. The results provide implications for adopting BIM in tourism industry and may help improve the efficiency of the industry. This study is still ongoing and findings are based on the current data collected. In future validation of data is needed to sustain the wetland tourism by using Building Information Modelling (BIM).